Systemic Infection by Methicillin-resistant Staphylococcus pseudintermedius in a Bitch - dos Santos, Jôiciglecia Pereira; Machado de Souza, Valesca Ferreira; Pereira, Zayan Silva; Carneiro, Ianei de Oliveira; Soares Frade, Maria Talita; Alves da Silva Vieira, Layze Cilmara (Acta Scientiae Veterinariae, 2021)
Background: Staphylococcus pseudintermedius is an opportunistic pathogen, belonging to the genus Staphylococcus. The methicillin-resistant Staphylococci have the mecA-gene, which confers them with the ability of becoming resistant to methicillin and multiple classes of antimicrobials, which makes the treatment of the affections caused by these specimens difficult. This work describes a case of systemic infection and death by methicillin-resistant S. pseudintermediusin a bitch. Case: A crossbred bitch (Canis lupus familiaris), was admitted to the University Veterinary Hospital of the Federal University of Western Bahia (HVU-UFOB). The main complaint reported by the owner was the presence of mammary nodules and constant nasal secretion. During the clinical examination was observed reactivity in the popliteal and left submandibular lymph nodes, pale mucous membranes, stomatitis, bilateral mucopurulent nasal secretion, abdominal pustules, serous secretion in the inguinal mammary gland and focal alopecia on the dorsum. On auscultation, was identified only arrhythmia and the other physiological parameters of the animal were within normality for the species. Samples of the nasal secretion and of the secretion from the abdominal pustules were collected, and sent to the Veterinary Microbiology Laboratory of the same institution. The samples collected were sown in 5% Blood Agar (BA), Sabouraud Agar (SAB) and MacConkey Agar (MCK), after 24 h was observed in BA the growth of macroscopically white colonies, with a humid aspect, creamy consistency, with presence of catalase and α-hemolysis. Microscopically, was observed the presence of Gram-positive cocci, suggestive of Staphylococcus sp. Microscopically, was observed the presence of Gram-positive cocci, suggestive of Staphylococcus sp. In the MALDI-TOF mass spectrometry, was identified S. pseudintermedius. Enrofloxacin [Enrotrat tab® 25 mg, 5 mg/kg, SID, PO, 5 days] was prescribed and a follow-up consultation was requested. Two weeks after leaving the University Veterinary Hospital, the animal was admitted in emergency and was submitted to the support protocol and died during the procedure. After the owner’s authorization, the anatomopathological examination was carried out, and fragments of the liver, lung and kidney were collected, in addition to sample of the liquid of the abdominal cavity for microbiological examination, and was evidenced the growth of S. pseudintermedius in all the specimens. The bacterium’s susceptibility to 19 antibiotics was tested, and a high degree of resistance was found, with sensitivity only to amoxicillin+ clavulanate (20-10 μg), chloramphenicol (30 μg) and vancomycin (30 μg). Given the detection of MRSP in Chromogenic Agar and in cefoxitin disks, all the specimens were MRSP positive. Discussion: The diagnosis based on the bacteriological culture and anatopathological findings were essential for the confirmation of the clinical presentation of septicemia. The isolation of S. pseudintermedius in all the analyzed samples, associated to the identification by MALDI-TOF Mass Spectrometry confirmed the clinical suspicion of systemic infection. Based on the result of the antibiogram and phenotypic tests, it was evidenced that all the isolates were MRSP positive, presenting multiple resistance to antibiotics, which may have interfered in the efficiency of the treatment. The results obtained in this report are worrying and signal the need for the implementation of phenotypical researches associated to anti-microbial susceptibility tests in bacteria isolated from animals attended in veterinary clinics and hospitals, in order to monitor and avoid the dissemination of pathogens with a multi-resistant profile.